Pemberitaan penganiayaan David Ozora pada media Kompas.com: analisis wacana berbasis korpus - Wijayanti, Astri; Firmonasari, Aprillia (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
Cases of violence against children have recently become more frequent. Therefore, many parties have also evaluated their performance in handling these cases. One of them is the police, who are never out of the public spotlight. This study aims to analyze the discourse and dissect the frame of the police image regarding the David Ozora persecution case through Kompas.com media. This research uses a descriptive qualitative method and a corpus discourse analysis approach. The research data was taken from news articles published in Kompas.com media. The results showed that the relevant keyword used in Kompas.com media to report the persecution case of David Ozora was "persecution." In addition, Kompas.com's media strategy is framing the image of the Police by mentioning positions and titles. The media also tends to use positive words to disseminate the image of the Police regarding the achievements and accomplishments in handling the persecution case. This research is linguistic research that can be useful for adding knowledge references, especially in the field of corpus linguistics.